Gender Differences in University Students' Levels of Physical Activity and Motivations to Engage in Physical Activity - María Espada; Nuria Romero-Parra; Daniel Bores-García; José Manuel Delfa-De La Morena (MDPI AG, 2023)
The transition of students to the university stage is a critical period in which there are numerous changes that could influence their lifestyles. The aim of this research was to analyse the levels of physical activity and the types of motivation for physical activity among university students according to gender. A quantitative, descriptive, and cross-sectional survey methodology was used. A total sample of 3060 university students, 47.8% women and 52.2% men, with a mean age of 20.88 ± 2.01 years was recruited. The sampling margin of error was ±1.85%. The short form of the International Physical Activity Questionnaire and the third version of the Behavioural Regulation in Exercise Questionnaire were used to evaluate MVPA and motivations to exercise, respectively. Two-way ANCOVA and a mediation analysis were performed. The most relevant results show that less than half of the university men and women are considered physically active. Furthermore, when analysing the interaction between motivation and gender, a large effect in identified motivation (F = 65.03; p≤ 0.001) and integrated motivation (F = 324.58; p ≤.0.001) and a medium one intrinsic motivation (F = 169.39; p ≤ 0.001) was found. Therefore, women university students have lower levels of physical activity practice than men students and show higher external motivation and demotivation.